KOINONIA DALAM SURAT FILEMON 1:6: SUATU ANALISIS TERHADAP RELASI FILEMON DAN ONESIMUS - Epafroditus Cahya Tantama (Phronesis: Jurnal Teologi dan Misi, 2022)
Fellowship (Greek: koinonia), as one of the church's vocations, should be able to bridge differences and change social life. However, the reality is the opposite. Christian fellowship sometimes becomes closed to people with certain social status differences. This paper aims to show that fellowship among believers can break down barriers and change lives. Through qualitative research that uses social and textual criticism methods on the Epistle of Philemon with the help of some related literature, an understanding is shown that an enslaved person who is guilty repents. Returns to his master are still counted in the Christian community and involved in the ministry. In the end, this paper concludes that a healthy Christian fellowship can transform lives. Within the Christian community, there is acceptance of one another and giving space for all people with different social statuses to actualize themselves in the life of the church, including in the community's social life.